Trend Analysis of Financial Ratios to Assess the Financial Performance of Construction Companies Listed on the Indonesia Stock Exchange During the 2020–2024 Period - Nurhanipah Nurhanipah; Muhammad Ihsan Rangkuti; Nur Aliah (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study examines the financial performance of profitable construction companies in Indonesia through trend analysis of key financial ratios, namely liquidity, profitability, and solvency. The study focuses on construction companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. A descriptive quantitative method with a financial ratio trend analysis approach is employed to assess changes in financial performance and identify potential future financial risks. The findings reveal that PT Adhi Karya Tbk shows an increasing trend in both the current ratio and net profit margin; however, these ratios remain below generally accepted benchmark standards. In contrast, the company’s debt to asset ratio demonstrates a declining trend and has reached an acceptable level, indicating an improvement in capital structure. PT Total Bangun Persada Tbk experiences a declining trend in its current ratio, which does not meet liquidity standards, while its net profit margin recovers and shows a positive trend after a decline in 2022. Although its debt to asset ratio increases, it remains within a favorable range. PT Pembangunan Perumahan (Persero) Tbk records an improvement in its current ratio, reflecting better liquidity, but its net profit margin exhibits a downward trend. The company’s debt to asset ratio decreases but remains above 50 percent, indicating relatively high leverage. Overall, the financial performance of the three companies varies and has not fully met ideal financial standards, highlighting the importance of improving liquidity, profitability, and leverage management to strengthen financial stability and competitiveness in the Indonesian construction industry.